Oestrogen receptor negative early operable primary breast cancer in older women—biological characteristics and long-term clinical outcome - Coleman, William B.; Syed, Binafsha Manzoor; Morgan, DAL; Setty, Tulassi; Green, Andrew R.; Paish, Emma C.; Ellis, Ian O.; Cheung, Kwok-Leung (Public Library of Science, 2017)
Background